EFEKTIFITAS PENETAPAN ROOM ALLOTMENT KEPADA ONLINE TRAVEL AGENT DI NIKKO BALI RESORT AND SPA - Putu Ayu Aryasih (JURNAL BISNIS HOSPITALITI, 2017)
As the role of Online Travel Agent is very important, the hotel should be able tomaintain good relations with the Online Travel Agent. One of the efforts madeby the hotel is to provide Allotment to Online Travel Agent that has a high levelof productivity.Nikko Bali Resort and Spa is one of the hotels that provide allotment totravel agents in order to compete to get maximum sales. Nikko Bali Resort andSpa allocates 60% allotment to be awarded to 8 Online Travel Agents in theform of Guaranteed Allotment and Regular Allotment, but not yet fully realized.Maximizing the productivity of Online Travel Agent has to be done sothat the management can take decisions in the future in terms of giving allotment,so it is known which Online Travel Agent is very potential in fulfilling allotmentprovided with promotional strategy applied